Jari Terampil Karya Mandiri; Stimulasi Motorik Halus Berbasis Play-Based Learning untuk Kesiapan Belajar Anak - Intisari Intisari; Nur Alim Amri; Sutra Awaliyah Darfin; Nidha Eka Restuti Munawir; Muqimah Surganingsih (ARDHI : Jurnal Pengabdian Dalam Negri, 2026)
Fine motor development is a fundamental prerequisite for academic readiness and independence in early childhood. Still, currently, challenges such as sedentary behaviour and screen exposure hinder the optimisation of these abilities. This community service program aims to implement a Play-Based Learning model of fine-motor stimulation to improve the physical and academic readiness of children at Tamalate State Kindergarten in Makassar City. The intervention program was conducted over two weeks through three main stimulation zones: Texture Zone (playdough and finger painting), Precision Zone (beading, origami, and cutting), and Manipulative Zone (busy board and puzzles). The target subjects were children in group B with fine-motor impairments, and the study evaluated 20 children using periodic observation checklists. The results showed a significant transformation, with 95% of children (19 out of 20 participants) experiencing an increase in achievement from the Starting to Develop (MB) category to Developing as Expected (BSH) and Developing Very Well (BSB). These findings confirm that a structured intervention through play zones is not only effective in strengthening intrinsic hand muscles and eye-hand coordination but also in building children's resilience and perseverance in learning. The program recommends integrating a micro-curriculum based on stimulation zones into daily learning plans and strengthening partnerships with parents to maintain consistency in children's development.